Immunoglobulins D and M mediate signals that are qualitatively different in B cells with an immature phenotype. - Alés-Martínez, J E (1988)
The CH family of murine B-cell lymphomas includes several members that are sensitive to growth inhibition when their membrane IgM (mIgM) receptors are cross-linked by anti-mu chain, anti-kappa chain, or anti-idiotypic antibodies. These lymphomas are IgM+, Ia+, and IgD +/- and resemble neonatal B cells in terms of their exquisite sensitivity to anti-IgM-mediated negative signaling as a model for tolerance induction. In this report, we describe the properties of one of these lymphomas, CH33, which had been transfected with a construct containing an allotypically different delta chain constant region and the heavy chain variable region fragment from S107 (T15 idiotype positive). This transfected cell line allowed us to investigate the possibility that membrane IgD (mIgD) and mIgM can mediate different signals. Our results show that the transfected cells retained their exquisite sensitivity to anti-IgM-mediated growth inhibition; however, crosslinking of IgD with anti-delta chain antibody did not inhibit their growth. Furthermore, even prolonged pretreatment with anti-IgD antibodies did not affect cell growth nor did it modulate the inhibitory effects of anti-IgM antibody. Moreover, identical results were obtained with clones of CH33 that express significant amounts of endogenous IgD. Thus, the failure of mIgD to deliver a negative signal does not reflect a defect in the transfected IgD but appears to be a general property of IgD in these cells. The mIgD was shown to mediate transmembrane signals because anti-delta chain treatment resulted in Ca2+ mobilization in transfected CH33 cells and capping of those receptors. We conclude that mIgD can mediate qualitatively different signals than mIgM can and that mIgD expression per se is not sufficient to change the functional phenotype of immature B cells.